Espécies não-nativas e o seu papel sobre a estruturação da diversidade de assembleias de peixes de água doce em riachos neotropicais - Santos, Bruno Rhanniery Batista dos (2021)
Threats on earth’s biodiversity may be promoting the sixth process of mass extinction, and the introduction of non-native species in freshwater aquatic ecosystems is responsible to promote biodiversity loss. The process of introduction jeopardizes fish assembalges’ structure, leading to extinctions in some cases, whereas in other cases it may contribute to the elevation of fish diversity. In this way, it is fundamental the comprehension of how the presence of non-native fish species affect different components of diversity in freshwater fish assembles, leading to the main goal of this study: investigate the role of non-native fish species on different aspects of fish assembles’ diversity in headwater streams and their relationship with the environment, using the Upper Parana River basin as our study region. To that, we: 1) registered fish species occurrence at 586 assemblages with the presence of native species or native and non-native fish species; 2) calculated species richness, taxonomic diversity, and functional diversity for each assemblage; 3) compared both groups mentioned with the Generalized Least Squares (GLS) method; and 4) evaluated the relationship between native and non-native fish species with the environment using a RLQ analysis. In the 586 headwater streams, we found a total of 159 species with 28 being considered as non-native fishes. The results showed that species richness and taxonomic diversity were different between the group of streams formed only by native species and those formed by native and non-native species, and there is no difference regarding functional diversity. The results found with RLQ analysis also demonstrated that the environment influences on species distribution, but this influence it is nod directly related to species traits. Possibly, the processes of environmental filters selection and/or human impacts existing on headwater stream’s fish assemblages of the Upper Parana River basin lead to the formation of assemblages with few species, taxa and traits, and the introduction of non-native fish species could promote an elevation in the number of species and taxa. Therefore, such processes are important to explain the occurrence of non-native fish species and the observed patterns.